Undiagnosed and Uncontrolled Hypertension and Access to Health Care among Residents of an Urban Area of Eastern Nepal: a Cross-sectional Study - Kasaudhan, S. M.; Ghimire, A.; Sharma, S. K.; Baral, D.; Jha, N.; Singh, S. B. (Kathmandu University Medical Journal, 2022)
Background The burden and complication of hypertension is increasing as most of the people living with hypertension are unaware of their condition and those who are already diagnosed with it do not have their blood pressure under control.Objective To assess the prevalence of undiagnosed and uncontrolled hypertension among residents of Itahari sub metropolitan city of eastern Nepal, along with its associated socio demographic and behavioral risk factors and access to health care services.Method Cross sectional study was conducted in five wards of Itahari, among 1161 participants, using population proportionate to sample size sampling technique. Face to face interview was conducted with participants for data collection applying semi– structured questionnaire and physical measurement like blood pressure, weight and height.Result Prevalence of hypertension was 26.5% including undiagnosed 11.0% and previously diagnosed 15.5%. Among diagnosed, 76.6% had uncontrolled blood pressure and 56.70% were taking anti-hypertensive medicine, and 7.8% were under Ayurvedic medicine. More than 70% participants preferred private health facility for treatment and 22.7% had faced financial barrier to seek healthcare. About 64% of participants did not visit health services or had visited only once in past six months. Increasing age, Body Mass Index (BMI), smoking status and positive family history were found to be significantly associated with hypertension at < 0.05 level.Conclusion Prevalence of hypertension is high and awareness regarding available health services in local primary health center and its utilization is lacking among participants. Regular screening program for hypertension and awareness program to disseminate the knowledge of availability of primary health center should be conducted.